Non-pharmaceutical interventions for containment, mitigation and suppression of COVID-19 infection (Colombia Medica, 2020)
The best available scientific evidence is required to design effective non-pharmaceutical interventions (NPIs) to help policymakers to contain COVID-19 outbreaks. The aim of this review is to describe which NPIs used different countries and a when they use them. It also explores how NPIs impact the number of cases, the mortality, and the capacity of health systems. We consulted eight web pages of transnational organizations, 17 of international media, 99 of government institutions in the 19 countries included, and besides, we included nine studies (out of 34 identified) that met inclusion criteria. We found that some countries are focused on establishing travel restrictions, isolation of identified cases, and high-risk people. Others have a more intense combination of mandatory quarantine and other drastic social distancing measures. Some countries have implemented interventions in the first fifteen days after detecting the first case, while others have taken more than 30 days. The effectiveness of isolated NPIs may be limited, but combined interventions have shown to be effective in reducing the transmissibility of the disease, the collapse of health care services, and mortality. When the number of new cases has been controlled, it is necessary to maintain social distancing measures, self-isolation, and contact tracing for several months. The policy decision-making in this time should be aimed to optimize the opportunities of saving lives, reducing the collapse of health services, and minimizing the economic and social impact over the general population, but principally over the most vulnerable. The timing of implementing and lifting interventions is likely to have a substantial effect on those objectives.